Survival prognosis evaluation in advanced breast cancer patients: a study on the application of the advanced lung cancer inflammation index - Liang, Chunfeng; Yang, Chunyan; Yang, Qiujiao; Tang, Yuchen; Zhang, Wenhai; Tan, Qixing; Qin, Qinghong (Frontiers in Oncology, 2025)
BackgroundInflammation and nutritional status play critical roles in tumor initiation and progression. Advanced Lung Cancer Inflammation Index (ALI) has gained widespread attention as a novel biomarker for cancer prognosis evaluation.MethodsThis retrospective study analyzed 163 advanced breast cancer patients with distant metastasis (Guangxi Medical University Cancer Hospital, 2016-2023). Patients were stratified into high-ALI (n=64) and low-ALI (n=99) groups via K-means clustering. Kaplan-Meier survival curves with log-rank testing were used to assess survival differences, while Cox proportional hazards models were employed to evaluate the independent prognostic value of ALI. The predictive performance of ALI was assessed using time-dependent ROC curves.ResultsHigh ALI correlated with superior overall survival (log-rank p=0.0024) [HR=2.493 (95%CI 1.350-4.606) p = 0.004]. Multivariate analysis confirmed ALI as an independent prognostic factor (HR=0.39, 95% CI 0.16-0.95, p=0.037). ALI demonstrated stable predictive accuracy with 3-year AUC=0.645 and 5-year AUC=0.650 (C-index=0.65). Subgroup analyses confirmed prognostic consistency across clinical characteristics (p-interaction>0.05).ConclusionALI is an independent prognostic factor for advanced breast cancer patients with good predictive ability. It provides an important supplementary prognostic marker for clinical practice and can help optimize personalized treatment strategies.